The Unforgettable Indus River Flood-2010: A Review - Ali, Arshad; Nosheen, Ghazala; Khan, K.A. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Floods are the unannounced natural disasters that destroy both lives and infrastructures. In July 2010 a huge and unpredictable flood struck Pakistan, especially the catchment area of the River Indus, extending from the north part of Khyber Pakhtun Khwa (KPK) Province south to the Arabian Sea. The top five rainfall intensities recorded at Risalpur, Islamabad, Murree, Cherat and Ghari Dopatta were 415mm, 394mm, 373mm, 372mm and 346mm, respectively. The Indus Flood-2010 affected nearly 20 million people spreading over 36 districts of the country. The death toll recorded was nearly 1,800 persons. More than 10 million people were subjected to contaminated drinking water. The destruction to cotton, rice, sugar cane, and animal fodder was recorded as 3,000 km2, 800 km2, 800 km2, and 1000 km2, respectively. And about five hundred thousand tons of wheat was destroyed. The Indus Flood of 2010 caused an estimated 43 billion US dollar loss to Pakistan and adversely affected its Gross Domestic Product (GDP). It brought on both the financial crises and socio-political concerns (such as infiltration of the Taliban in the form of a relief supporter). Though this flood has left everlasting impacts on the people of Pakistan, they could be better handled if the government and relief agencies were more determined, honest and committed. DOI: http://dx.doi.org/10.3126/hn.v9i0.7073 Hydro Nepal Vol.9 July 2011 48-51